2012
DOI: 10.1016/j.athoracsur.2011.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Postesophagectomy Chylothorax: Incidence, Risk Factors, and Outcomes

Abstract: Background Chylothorax is a rare but potentially lethal complication of esophagectomy. The study aims were to evaluate the rate of postesophagectomy chylothorax, identify associated risk factors and compare postoperative outcomes with patients who do not develop chylothorax. Methods We reviewed 892 consecutive patients undergoing esophagectomy (1997-2008). Preoperative, operative and postoperative details, including adverse outcomes and mortality, were analyzed. Results We identified postesophagectomy chyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 16 publications
(23 reference statements)
7
114
2
2
Order By: Relevance
“…Due to this low incidence, there is very few evidence on its predisposing factors and its optimal treatment of choice. Occurrence of chylothorax in postoperative period is associated with increase in the incidence of major complications and in hospital mortality by several folds [4]. Also, since the introduction of neoadjuvant therapy in the multimodality treatment of esophageal cancer, its impact on incidence of postoperative chylothorax is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this low incidence, there is very few evidence on its predisposing factors and its optimal treatment of choice. Occurrence of chylothorax in postoperative period is associated with increase in the incidence of major complications and in hospital mortality by several folds [4]. Also, since the introduction of neoadjuvant therapy in the multimodality treatment of esophageal cancer, its impact on incidence of postoperative chylothorax is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Shah and colleagues reported significant failure of conservative management if patients continued to have chest tube output over 11 cc/kg/d after beginning the treatment [44]. Dugue and colleagues used an output of chyle based upon body-weight ratio as an indicator of conservative treatment success and suggested that an output of less than 10 cc/ kg/d at day 5 of conservative treatment is justification to continue conservative management [24].…”
Section: Conservative Managementmentioning
confidence: 98%
“…Chylotorax is a rare complication after thoracic surgery, occurring in 0.5% to 2% after esophagectomy (35,36) and 1.4% to 2.3% after lung resection (37,38). Even rare, chylothorax can be a difficult complication leading to immunologic compromise, pneumonias and death in up to 30% of patients (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%